1986
DOI: 10.1002/kin.550180602
|View full text |Cite
|
Sign up to set email alerts
|

Effects of nonionic, cationic, and anionic micelles on the kinetics of the complexation reaction of nickel (II) with pyridine-2-azo-p-dimethylaniline

Abstract: The stopped-flow technique has been used to study the effect of cationic (CTAN), nonionic (Triton X-loo), and anionic (SDS) micelles on the rate of the reaction between nickel(I1) ion and the ligand pyridine-2-azo-p-dimethylaniline (PADA) at 20.0"C and ionic strength 0.03 mol dm-3. The complex formation reaction is markedly inhibited by both CTAN and Triton X-100 micelles. The kinetic data are found to conform to a reaction mechanism which implies only partitioning of the ligand between water and the micellar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1993
1993
2007
2007

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…The kinetic parameters of this reaction, as obtained through the Robinson version of the pseudophase model for micellar catalysis, are sensitive to variations in micelle structure and dynamics. The use of nonionic or cationic surfactants causes inhibition of the complexation . Reinsborough et al investigated the influence of the addition of cations on the catalytic effect produced by micelles, as well as the influence of the micellar structure and the effect exerted by zwitterionic surfactant solutions .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The kinetic parameters of this reaction, as obtained through the Robinson version of the pseudophase model for micellar catalysis, are sensitive to variations in micelle structure and dynamics. The use of nonionic or cationic surfactants causes inhibition of the complexation . Reinsborough et al investigated the influence of the addition of cations on the catalytic effect produced by micelles, as well as the influence of the micellar structure and the effect exerted by zwitterionic surfactant solutions .…”
Section: Introductionmentioning
confidence: 99%
“…The use of nonionic or cationic surfactants causes inhibition of the complexation. 11 Reinsborough et al investigated the influence of the addition of cations on the catalytic effect produced by micelles, 12 as well as the influence of the micellar structure 13 and the effect exerted by zwitterionic surfactant solutions. 14 The studies on micellar systems were extended using fluorate surfactants 15 and mixtures of surfactants 16 and included the effect exerted by additives such as alcohols 17 and ureas on micellization.…”
Section: Introductionmentioning
confidence: 99%
“…16 #20 micelle and water using the relationship between the formation rate of their nickel(II) complexes and the concentration of the micelle. An inhibition effect of Triton X-100 micelle on the rate of formation of nickel(II) with pyridine-2-azo-p-dimethylaniline has been reported by Carbone et al, 18 and the phenomenon can be well explained only by the partitioning of the ligand between water and the pseudophase. In these studies, the deceleration effect found in the present study was not observed.…”
Section: Correction For the Rate Of Complex Formation With Htfa In Trmentioning
confidence: 80%
“…Therefore in the present case the reaction shown in scheme 1 applies. Such a scheme has been proposed by Carbone et al to explain the complex formation 14 between Ni(II) and pyridine-2-azo p-dimethyl aniline. The apparent rate constant is m k given by 2 Since the rate decreases from a maximum as the anionic surfactant concentration increases, k w can be neglected with respect to the other term in the numerator of (2) and the rearrangement of this expression yields Examination of the binding constants reveals that K s values are much larger than K o values.…”
Section: Experimental -Materials and Methodsmentioning
confidence: 96%